A novel full-length KIR3DS1*0130106 allele identified by sequencing - Wang, L; Zhang, Y; Dong, T; Rowland-Jones, S; Yindom, L (Blackwell Publishing Ltd, 2014)
The novel KIR3DS1*0130106 differs from KIR3DS1*0130101 with a single point mutation at position 7211 (G>T). © 2014 John Wiley and Sons A/S. Published by John Wiley and Sons Ltd.